Improving Students Learning Outcomes by Using Cooperative Learning with Student Teams Achievement Divisions (STAD) type - Sholahudin Al Ayubi (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2017)
The purpose of the research to describe the using of cooperative learning model with Student Teams Achievement Divisions (STAD) type in students learning outcomes and to know what the using of cooperative learning model with Student Teams Achievement Divisions (STAD) type can increase the students learning outcomes.  The kind of the research is PTK with qualitative and quantitative approach. The subjects of the research are students of class VIIA at SMP 02 Islam 45 Ambulu. With the data collecting method that used in the research are documentation, observation, interview and test. The data analysis method that used is qualitative and quantitative. The results of the research there is increased student learning outcomes.Keywords: STAD, students learning outcomes